Visual Representations in Indonesian Chemistry Textbooks: Supporting Deep Learning for 2025 Educational Goals - Ridhani, Jovita; Trisnaningsih, Sari; Fitriani, Ika Nur (Indonesian Journal of Instructional Media and Model, 2025)
Indonesian students struggle with abstract science concepts, as reflected in their low performance in international assessments. The primary learning resource is still textbook, and their visual materials are significant in helping students understand abstract concepts, especially in chemistry. However, visuals are often underutilized in science education. To address this gap, this study analyzes visual representations in Indonesian chemistry textbooks of the 2013 Curriculum to inform future improvements aligned with Indonesia’s 2025 educational goals. Two widely used textbooks for grades X and XII were examined to explore differences across grades. Using qualitative content analysis and a modified rubric, the study reveals that symbolic visuals that have explicit surface features (such as chemical formula and equations) dominate, while macroscopic and sub-microscopic visuals are underrepresented. In relation to the text, most visuals are completely related with the content but not directly referred to in the text, which may hinder students’ understandings. Positively, most visuals are contiguous (positioned close to the related text) with the related text and categorized as either with-caption or incorporated into text. These findings highlight gaps in textbook design, such as overreliance on symbolic visuals and poor visual-text integration. To support deep learning, textbooks should include multi-level visuals, ensure direct referencing, and provide clear captions. These changes are essential for fostering deeper understanding and aligning with Indonesia’s 2025 educational goals, offering insights for improving textbook quality. Indonesian students struggle with abstract science concepts, as reflected in their low performance in international assessments. The primary learning resource is still textbook, and their visual materials are significant in helping students understand abstract concepts, especially in chemistry. However, visuals are often underutilized in science education. To address this gap, this study analyzes visual representations in Indonesian chemistry textbooks of the 2013 Curriculum to inform future improvements aligned with Indonesia’s 2025 educational goals. Two widely used textbooks for grades X and XII were examined to explore differences across grades. Using qualitative content analysis and a modified rubric, the study reveals that symbolic visuals that have explicit surface features (such as chemical formula and equations) dominate, while macroscopic and sub-microscopic visuals are underrepresented. In relation to the text, most visuals are completely related with the content but not directly referred to in the text, which may hinder students’ understandings. Positively, most visuals are contiguous (positioned close to the related text) with the related text and categorized as either with-caption or incorporated into text. These findings highlight gaps in textbook design, such as overreliance on symbolic visuals and poor visual-text integration. To support deep learning, textbooks should include multi-level visuals, ensure direct referencing, and provide clear captions. These changes are essential for fostering deeper understanding and aligning with Indonesia’s 2025 educational goals, offering insights for improving textbook quality.